A New Second Order Numerical Scheme for Solving Decoupled Mean-Field FBSDEs with Jumps (Journal of Computational Mathematics, 2024)
In this paper, we consider the numerical solution of decoupled mean-field forward backward stochastic differential equations with jumps (MFBSDEJs). By using finite difference approximations and the Gaussian quadrature rule, and the weak order 2.0 Itô-Taylorscheme to solve the forward mean-field SDEs with jumps, we propose a new second orderscheme for MFBSDEJs. The proposed scheme allows an easy implementation. Some numerical experiments are carried out to demonstrate the stability, the effectiveness and thesecond order accuracy of the scheme.